Crumbs, a component of the apical membrane, is required for zonula adherens formation in primary epithelia of Drosophila. - Tepass, U. (Developmental Biology, 1996)
The zonula adherens (ZA) is a cell-cell adherens junction that forms a belt in the apical most region of the lateral cell surface of many epithelia. It is composed of the cadherin-catenin complex and many associated proteins and is connected to a prominent belt of microfilaments. The ZA is believed to play an important role in the differentiation and behavior of epithelial tissues and thus contributes substantially to embryonic morphogenesis. In Drosophila embryos the ZA is formed during and shortly after gastrulation from adherens junction material that appears on the cell surface during cellularization. A ZA is present in a subset of epithelia in the Drosophila embryo called primary epithelia. A second specific marker for primary epithelia is the Crumbs protein, which in concert with the gene product of stardust is required to maintain epithelial polarity. This report shows that both genes are required for the reorganization of adherens junction material into the ZA. Using immunoelectron microscopy it is shown that Crumbs is not a component of the ZA but is distributed over the entire apical cell surface and concentrated in the immediate vicinity of the ZA. These results indicate a rather direct requirement of an apical activity for the organization of the lateral membrane domain in Drosophila primary epithelia. It is proposed that the marginal zone of the apical cell surface contains a crumbs- and stardust-dependent retention mechanism for adherens junction material that aids in the formation of the ZA.